Two new species of Halictophagus (Strepsiptera, Halictophagidae) from the Dominican Republic - Cook, Jerry L. (Zootaxa, 2013)
Halictophagus trigonodontos Cook, n. sp. and Halictophagus dominicus Cook, n. sp. are described from the Dominican Republic. The stout and heavily-sclerotized mandibles of H. trigonodontos are unusual for the genus. The genus Halictophagus and the subfamily Halictophaginae have previously been characterized as having non-sclerotized mandibles. However, H. trigonodontos and H. dominicus have sclerotized mandibles, as do other previously describes Halictophagus species. The subfamily Halictophaginae, including genera Halictophagus and Stenocranophilus, can still be separated from Coriophaginae by not having a head capsule with sulci and sutures as is found in Coriophaginae.